Implementation Of Differentiated Learning In Class V Pancasila Education Subjects In Primary Schools - Mahmudi, Khoirudin Nur; Saputro, Bagus Ardi; Reffiane, Fine; Cindy Ayu, Angela Astrid Stelladiba (DIDAKTIKA, 2024)
This research aims to describe the application of differentiated learning in Pancasila education subjects in the fifth grade of elementary schools in Semarang. Differentiated learning means teachers adapt teaching methods to different learning styles among students. This research used descriptive qualitative methods with 28 students as subjects. Data is collected through observation and documentation. The research results show that students have various learning styles, with the visual style being the most dominant, followed by auditory and kinesthetic. In implementing differentiated learning, students are given the freedom to produce learning products according to their respective learning styles. This application creates a learning atmosphere that is collaborative, fun and full of enthusiasm, so that students can learn according to their interests and needs. This makes learning more meaningful for students. Overall, this research emphasizes the importance of adapting learning methods to the needs and characteristics of students so that the learning process is more effective and memorable.Keywords: Differentiated Learning, Pancasila Education, Student Learning Styles